2020
DOI: 10.3390/ijms21134698
|View full text |Cite
|
Sign up to set email alerts
|

Role of ROS/RNS in Preeclampsia: Are Connexins the Missing Piece?

Abstract: Preeclampsia is a pregnancy complication that appears after 20 weeks of gestation and is characterized by hypertension and proteinuria, affecting both mother and offspring. The cellular and molecular mechanisms that cause the development of preeclampsia are poorly understood. An important feature of preeclampsia is an increase in oxygen and nitrogen derived free radicals (reactive oxygen species/reactive nitrogen species (ROS/RNS), which seem to be central players setting the development and progressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 172 publications
(224 reference statements)
0
8
0
Order By: Relevance
“…Oxidative stress is observed in PE, where the levels of ROS are elevated, resulting in impaired NO signaling and vascular dysfunction. In PE, excess levels of all ROS are reported to be more prevalent, including superoxide superoxide (O 2 ·), hydrogen peroxide (H 2 O 2 ), hydroxyl radical (OH) and peroxynitrite (ONOO−) ( Agarwal et al, 2005 ; Rozas-Villanueva et al, 2020 ). In our work presented, we successfully constructed an oxidative stress model in vitro in cultured TEV-1 cells by H 2 O 2 treatment (500 μM, 3 h) that significantly induced ROS levels to 1.8 folds, which is consistent with previous reports ( Haendeler et al, 2005 ; Gao et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is observed in PE, where the levels of ROS are elevated, resulting in impaired NO signaling and vascular dysfunction. In PE, excess levels of all ROS are reported to be more prevalent, including superoxide superoxide (O 2 ·), hydrogen peroxide (H 2 O 2 ), hydroxyl radical (OH) and peroxynitrite (ONOO−) ( Agarwal et al, 2005 ; Rozas-Villanueva et al, 2020 ). In our work presented, we successfully constructed an oxidative stress model in vitro in cultured TEV-1 cells by H 2 O 2 treatment (500 μM, 3 h) that significantly induced ROS levels to 1.8 folds, which is consistent with previous reports ( Haendeler et al, 2005 ; Gao et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of pregnancy-induced hypertension is not fully explained, but the pathogenesis of PE takes into account disturbances in trophoblast invasion into the walls of the spiral arteries, which results in a lack of remodeling, high-resistance circulation, and placental ischemia [37,38]. The balance of many placental biomarkers is disturbed, oxidative stress and inflammation in both the placenta and in the mother's circulation are intensified, and the effect is endothelial function damage and an increase in blood pressure [16,[37][38][39]. There are many studies available in the literature which have found associations between lower levels of antioxidants in pregnant women with PE [40].…”
Section: Discussionmentioning
confidence: 99%
“…Following ICH progression, the accumulation of ROS induces oxidative stress, which contributes to SBI caused by inflammation and BBB disruption [ 4 ]. Interestingly, ROS/RNS are involved in regulating the change of connexin and pannexin-based channel properties, both in systemic vasculature and brain cells [ 58 , 59 ]. Moreover, oxidation products were shown to increase hemichannel activity whilst reducing GJIC [ 60 ].…”
Section: Connexin and Pannexin Channels In Ichmentioning
confidence: 99%